The Normative Leadership And Work Discipline Of Public Officials: Key Determinants Of Successful Urban Village Development In The Era Of Regional Autonomy - Fotris Junimiati Sanjaya; Ernani Hadiyati; F.X. Bhakti Hendrakusuma; Yosar Haritsar (Management Study Program, Faculty of Economics, Merdeka University Pasuruan. East Java. Indonesia, 2026)
The success of development at the urban village level is largely determined by the quality of local governance, particularly leadership styles and employee discipline. This study aims to analyze the implementation of normative leadership patterns and work discipline among apparatus members, as well as their contribution to development in Kraksaan Wetan Urban Village, Probolinggo Regency. A qualitative descriptive approach was employed in this research. Data collection techniques included in-depth interviews, field observations, and document studies. The informants consisted of the village head, division heads, village staff, and community leaders. The findings reveal that normative leadership, which emphasizes role modeling, rule enforcement, and fairness, significantly improves work discipline among the apparatus. Supporting factors for work discipline include a consistent supervision system, transparent reward and punishment mechanisms, and a professional work culture. The synergy between normative leadership and high work discipline accelerates the implementation of both physical development and community empowerment programs. This study confirms that simultaneously strengthening leadership and work discipline serves as a key strategy for achieving effective, accountable, and sustainable development at the urban village level.